Pengembangan Modul Tata Surya Berbasis Augmented Reality Terintegrasi Etnosains untuk Meningkatkan Keterampilan Pemecahan Masalah Siswa Kelas VII SMP: Development of Ethnoscience-Integrated Augmented Reality-Based Solar System Module to Improve Problem-Solving Skills of Junior High School Grade VII Students - Febrianto Putra; Arini Rosa Sinensis; Renita Nurhalis Fitriani (U-Teach: Journal Education of Young Physics Teacher, 2026)
This research aims to develop an innovative Augmented Reality (AR)-based Solar System learning module that is integrated with ethnoscience to improve the problem-solving skills of grade VII junior high school students. This module was developed using a Research and Development (R&D) approach with the ADDIE model, which incorporates AR features through the Assemblr Edu application. Expert validation by content and media specialists resulted in eligibility scores of 91.3% and 82.4%, respectively—both of which were categorized as highly feasible. During the implementation phase, trials were conducted in three stages: individual (75%), small group (82.67%), and field (89%), with student responses ranging from good to excellent. Effectiveness testing through pretest and posttest showed a significant increase in the average score from 37.83 to 79.13, achieving an N-Gain of 0.715 (high category). The integration of ethnoscience successfully provides a contextual connection between abstract astronomy concepts and the students' cultural environment, thereby increasing engagement, understanding, and problem-solving skills. The results, which show the great potential of the AR-ethnoscience module in fostering high-level thinking skills and supporting the Independent Curriculum, underlie recommendations for future research to expand its implementation to other abstract science materials, such as vibration and waves, as well as measure their impact on long-term memory, self-efficacy, and learning motivation in various school characteristics